PENINGKATAN PEREKONOMIAN EKS TENAGA KERJA WANITA MELALUI KERAJINAN BERBASIS KEARIFAN LOKAL DI DESA KRADENAN KECAMATAN PURWOHARJO KABUPATEN BANYUWANGI - M. Amir Mahmud; Iis Ni’matul Jannah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2020)
One of the opportunities that can be used to create new employment opportunities and also have the potential to improve the family economy of former women workers is by providing them with skills based on local wisdom. The purpose of this service is to improve the economy of Indonesian ex-female labor through handicrafts based on local wisdom in Kradenan Village, Purwoharjo District. The strategy undertaken is to provide understanding, knowledge, insight and skills for Indonesian ex-female labor. The results of her dedication show that this former female worker has a new awareness of entrepreneurship. This is shown by their seriousness in following the bamboo handicraft training. The effort to make handicrafts makes the Indonesian ex-female labor more empowered to have skills and the job opportunities are open automatically as a result, the Indonesian ex-female labor are more empowered and do not want to return to being female workers.